A 1 year 2 months old child with Kawasaki Disease- A Case Report: Kawasaki Disease - Alam, Mohammad Mahbubul; Khatoon, Nushura; Hoque, Saidul; Karim, Enamul; Hossain Mollah, Delwar; Kumar Ghosh, Susanta (Journal of the Medical College for Women & Hospital, 2025)
Kawasaki disease (KD) is a self-limiting and acute median vessels vasculitis of causes that are unknown and takes place predominantly in infants and children. The disease in its acute phase is self-limited and the diagnosis may be missed; if untreated, KD can result in aneurysm of the coronary artery in 25% of patients. Principal criteria for diagnosing the disease is fever of more than 5 days and presence of a minimum of following 4 principal features: erythema and cracking of lips, strawberry tongue, bilateral non-purulent conjunctival injection, rash, erythema and edema of the hands or feet, cervical lymphadenopathy >1.5cm, usually unilateral. Our patient presented with all the above features. Additional features like irritability, arthritis, desquamation, vomiting, diarrhea, abdominal pain, Bacillus Calmette-Guérin (BCG) induration. Diagnosis of KD is mainly clinical, but anemia, neutrophilic leukocytosis, thrombocytosis, raised Erythrocyte Sedimentation Rate (ESR) , raised aminotransferase, raised C-Reactive Protein (CRP), reduced serum albumin, pyuria may be present. The investigation findings of this patient indicated towards the diagnosis of KD. Echocardiogram was done and coronary artery dilatation was noted. The patient was managed using a single dose of intravenous immunoglobulin(IVIG) 2g/kg administered over a period of over 10 hours which was followed by aspirin 75mg/kg until the patient became afebrile. This dose of aspirin was continued for another 3 days then 5mg/kg of aspirin was given for 8 weeks. During follow-up the patient’s condition was uneventful. J Med Coll Women Hosp.2025; 21 (2):157-162